Strategi Komunikasi Visual Melalui Media Sosial: Studi Kasus Pada Akun Instagram Tirtoid - Kristanti, Agnes Indah Suciani; Buntaran, Louis Cahyo Kumolo (Visualita Jurnal Online Desain Komunikasi Visual, 2024)
Tirtoid is a news platform that has been in operation since 2016 and has successfully targeted the 20 to 30-year-old reader demographic by offering the latest news in a lighter and more enjoyable format, wrapped in an appealing infographic shape. Tirtoid articles have a light language style and frequently use contemporary terminology. The study focuses on the communication strategies employed by the news provider platform Tirtoid to create news that appeals to the younger generation market, using observation methods on 11 Tirtoids graphical content from January 1 to January 7, 2023, as well as paper reviews. This study discovered that standardization in the form of content management is an effective communication approach to preserve consistency and relate to connections (relate), positive This research has revealed that standardization in the form of content management is an effective communication strategy for maintaining consistency and relating to connections (relate), positive relationships, trust (engagement), and success (success) in effectively delivering messages to the target audience.